Pelaksanaan Literasi Al-Qur’an Melalui Program Rutin Tahfizh Al-Qur’an Di Kelas Ix Mtsn 7 Agam - Mansyah, Iqbal Doni; Dewi, Puti Andam; Saleh, Syafril (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Memorizing the Qur’an is an activity that everyone can do. The large number of people memorizing the Al-Quran is one way to maintain the purity of the Al-Quran, so lucky are those people who can maintain the Al-Quran by memorizing it. Because the Al-Quran itself is the word of Allah which functions as a guide and guidance for mankind, to understand the contents of the Al-Quran by memorizing and practicing it in everyday life. A memorizer of the Al-Quran is required to have a high interest in the Al-Quran, both in the process of memorizing and at the end of memorizing. One of them is by knowing the virtues and wisdom in reading and memorizing the Al-Quran. However, memorizing theAl-Quran is not an easy matter but it is also not something that is impossible nowadays,because at the time of the Prophet many people memorized the Qur'an. The research location is at MTsN 7 Agam. This type of research is field research. Field research is research carried out in the community or school to provide a complete picture of a situation. The approach used is a qualitative descriptive approach. The approach, where this research has a distinctive characteristic, is that it lies in its objectives. A descriptive approach is research to explore and clarify a phenomenon and the reality that occurs, namely by describing a number of variables related to the problem being studied. Based on research, the Al-Qur'an literacy program at Madrasah Tsanawiyah Negeri 7 Agam is carried out by carrying out routine tahfizh for 1 hour of learning after the Dhuha prayer and before the start of study hours at school as well as special lesson hours for tahfizh subjects. This Al-Qur'an literacy program is a mandatory program at Madrasah Tsanawiyah Negeri 7 Agam which is included in the mandatory lesson schedule. Al-Qur'an literacy programs vary in each school. At MTsN 7 Agam, the Al-Qur'an literacy program through tahfizh activities is carried out by memorization and deposit and is tested for the special tahfizh subject. If students have memorized several juz then a tahfizh graduation event will be held at MTsN 7 Agam.